Career Self-Management Scale (CEDLE scale) In The Indonesian Version of The Social Cognitive Model - Nur Fadhilah Umar; Abdullah Sinring; Abdullah Pandang (Indonesian Journal of Educational Studies, 2022)
Abstract. This study aimed to measure the adaptability of the Indonesian version of the Career Self-Management Scale (CEDLE Scale) and obtain a model fit from that scale. The CEDLE Scale was developed by Lent, et al in 2017. The process of adapting the CEDLE scale using the backward-translation technique method is translating the original scale into the Indonesian version, consulting with linguists, and translating back to the original language version. The population in this study were students in the province of South Sulawesi who registered in the 2021/2022 academic year. The sampling technique used stratified random sampling. The sample of this research is 320 students; 170 females and 150 males. This research instrument uses the CEDLE scale, which consists of 3 (three) indicators, namely Personal mastery (PM), Verbal persuasion (VP), and Vicarious learning (VL). The CEDLE scale consists of 12 items, and 8 items related to the emotions felt when conducting career exploration. The data analysis technique used a validity test concerning the corrected correlation item value and item reliability concerning Cronbach and McDonald's alpha values. Furthermore, the data were analyzed using confirmatory factor analysis (CFA). The results showed that the adaptation of the CEDLE scale was in the Fit Index category with values of chi-square (90.263/51), RMSEA (0.053), GFI (0.950), CFI (0.963), GFI (0.952).